Fostering Student Agency: The Application of Emancipatory Education Principles within Indonesia's Merdeka Curriculum - Sheptian, Riky; Tjalla , Awaluddin; Soeprijanto (Indonesian Scientific Publication, 2026)
This study investigates the implementation of emancipatory education principles within Indonesia’s transformative Merdeka Curriculum, a paradigm that promotes flexible and student-centered learning to strengthen adaptability and critical thinking. Using a descriptive qualitative approach with a case study design at Al Khoiriyah Al Husna Islamic Elementary School in Sukabumi, data were collected through participatory observations in 12 learning sessions, in-depth interviews with 26 teachers, focus group discussions, and document analysis involving 60 students from grades 4 to 6. The findings reveal significant pedagogical transformations, including increased student participation, enhanced project-based learning practices, and improved digital assessment systems, although challenges remain in mindset change, capacity building, and technology integration. The study concludes that emancipatory education can be effectively operationalized within the Merdeka Curriculum and leads to substantial transformation in traditional classrooms. It implies that sustained professional development and supportive institutional frameworks are critical for ensuring the continuity and scalability of transformative educational practices in Indonesia.